The Impact of Tourism Development on the Social and Economic Conditions of the Community in Nusa Lembongan Island - Anita Carolina Wijaya; Heri Puspito Diyah Setiyorini (Jurnal Pendidikan Ilmu Sosial, 2024)
Tourism plays a pivotal role in the economic and social dynamics of destinations worldwide, including Nusa Lembongan Island within the Klungkung Regency, Bali. This study investigates the multifaceted impacts of tourism on the local community of Nusa Lembongan, focusing on economic and social dimensions. Using a mixed-methods approach, qualitative data was gathered through interviews and observations, complemented by quantitative data on tourist arrivals and local demographics.Results indicate that tourism has significantly bolstered economic opportunities on the island, particularly through increased employment and income generation, albeit with varying distributional impacts across different segments of the population. Local residents have transitioned from traditional livelihoods such as seaweed farming to diverse roles within the tourism sector, benefiting from higher earnings and expanded job prospects. However, challenges such as inflationary pressures on essential goods and uneven distribution of tourism benefits persist, affecting overall community welfare.